Wood-based solid biofuel in Malaysia: export status and policy review - Jesuet, Melissa Sharmah Gilbert; Samdin, Zaiton; Saadun, Norzanalia (Asian Energy Studies Centre, 2024)
The widespread use of fossil fuel has led to severe environmental consequences, such as climate change and pollution. As a remedial response, the global energy landscape has decidedly shifted from fossil fuels to renewable energy sources, such as solar energy and biofuel for bioenergy. As a country rich in resources, Malaysia has had a golden opportunity to dwell on the production of the second-generation biofuel, also known as the wood-based solid biofuel (WBSB). This review paper intends to provide an overview of Malaysia’s WBSB production and export industry, focusing on the current export status for the products and the policy frameworks that support the industry in Malaysia. The export status of five WBSB products (wood pellet, briquettes, charcoal, fuelwood, and wood chips or particles) are appraised based on its export status and global ranking. In addition, related biomass or biofuel policy and the effect it has on the progression of the biofuel industry were analyzed and consolidated. The findings show that the biofuel industry in Malaysia, specifically those concerning WBSB is average at best compared to its neighbors in Southeast Asia, Vietnam and Indonesia in the export of wood pellets and charcoal, respectively. However, in recent years, Malaysia has become increasingly competitive in the export of pellets and chips, which are becoming one of the top 10 global exporters. Furthermore, government policies and initiatives aimed at promoting sustainable forestry practices and stimulating the bioenergy sector have facilitated the growth of the biofuel industry, such as the Green Technology Financing Scheme (GTFS) IV of the National Biomass Action Plan. In general, this review outlines the current export state of WBSB products, while highlighting the key policies that govern biomass and biofuel production to identify areas for potential improvement to enhance competitiveness and sustainability in Malaysia’s biofuel industry.